Pengaruh Kebijakan Dividen dan Profitabilitas Terhadap Kekayaan Pemegang Saham pada Indeks High Dividend 20 Periode 2019-2023 di Bursa Efek Indonesia - Rani Yuliandri; Muslimin Muslimin; Ahmad Faisol (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyze the effect of dividend policy and profitability on shareholder wealth in companies listed in the High Dividend 20 Index on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research adopts a quantitative approach using secondary data obtained from the official IDX website (www.idx.co.id ).The population includes all issuers in the High Dividend 20 Index during the research period, and purposive sampling was applied to select 12 companies as the final sample. Data analysis techniques involved classical assumption testing, multiple linear regression, and hypothesis testing to determine the influence of independent variables on shareholder wealth. The statistical analysis was performed using EViews 12 Student Version software.The findings reveal that the Dividend Payout Ratio (DPR) does not have a significant effect on shareholder wealth, implying that dividend distribution is not the main factor influencing investor value in the observed companies. In contrast, Return on Assets (ROA) demonstrates a significant positive effect, which highlights the importance of profitability in driving shareholder wealth. These results suggest that investors may place greater emphasis on a company’s ability to generate earnings rather than its dividend distribution policy when assessing firm value. The study contributes to the literature on dividend policy and corporate performance by providing evidence from the Indonesian capital market, particularly within firms that consistently distribute high dividends.